Thermoplastic polymer composition and method for producing same

By using fluororesin, dynamic crosslinked fluoroelastomer and magnesium oxide in thermoplastic polymer composites, the problems of low production efficiency and insufficient flexibility of existing composite materials are solved, and thermoplastic polymer composites with high productivity and excellent flexibility are achieved.

JP7667513B2Active Publication Date: 2025-04-23DAIKIN INDUSTRIES LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2024119544
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2023-07-27
Filing Date
2024-07-25
Publication Date
2025-04-23
Estimated Expiration
2044-07-25

AI Technical Summary

Technical Problem

The existing thermoplastic polymer composite materials are inefficient and have insufficient flexibility during the production process, making it difficult to meet the application requirements of high productivity and excellent flexibility.

Method used

The thermoplastic polymer composite material containing fluororesin (A), dynamic crosslinked fluoroelastomer (B) and magnesium oxide (C) is used. The fluororesin is a copolymer of ethylene and tetrafluoroethylene (TFE). The crosslinked fluoroethylene under the melting conditions of fluororesin, magnesium oxide and crosslinking agent. The particle size of the magnesium oxide is less than 1.0 microns, and the mass ratio of fluororesin to crosslinked fluoroethylene is 50/50 to 95/5.

Benefits of technology

Thermoplastic polymer composite material that achieves high productivity and excellent flexibility properties is suitable for a variety of high-performance applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007667513000004
    Figure 0007667513000004
  • Figure 0007667513000005
    Figure 0007667513000005
  • Figure 0007667513000001
    Figure 0007667513000001
Patent Text Reader

Abstract

To provide a thermoplastic polymer composition which can be produced with high productivity and has excellent flex resistance.SOLUTION: The thermoplastic polymer composition containing a fluororesin (A), a crosslinked fluororubber (B) and magnesium oxide (C) is provided. The fluororesin (A) is a copolymer containing an ethylene unit and a tetrafluoroethylene unit. The crosslinked fluororubber (B) is obtained by dynamically crosslinking a fluororubber (b) in the presence of the fluororesin (A), the magnesium oxide (C) and a crosslinking agent (D) under a melting condition of the fluororesin (A). The volume-based 10% particle diameter of the magnesium oxide (C) is 1.0 μm or less. The mass ratio ((A) / (B)) of the fluororesin (A) to the crosslinked fluororubber (B) is 50 / 50-95 / 5.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to thermoplastic polymer compositions and methods for making the same. [Background technology]

[0002] Patent Document 1 describes a thermoplastic polymer composition comprising 10 to 95% by weight of a fluororesin (A) and 90 to 5% by weight of a crosslinked fluororubber (B), in which the fluororesin (A) comprises a fluorine-containing ethylenic polymer (a) having a melting point of 120 to 330°C, and the crosslinked fluororubber (B) is obtained by dynamically crosslinking at least one kind of fluororubber (b-1) or fluorine-containing thermoplastic elastomer (b-2) under melting conditions in the presence of the fluororesin (A) and a crosslinking agent (C). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] International Publication No. 2006 / 057331 Summary of the Invention [Problem to be solved by the invention]

[0004] An object of the present disclosure is to provide a thermoplastic polymer composition that can be produced with high productivity and has excellent flex resistance. [Means for solving the problem]

[0005] According to the present disclosure, there is provided a thermoplastic polymer composition containing a fluororesin (A), a crosslinked fluororubber (B) and magnesium oxide (C), wherein the fluororesin (A) is a copolymer containing ethylene units and tetrafluoroethylene units, and the crosslinked fluororubber (B) is obtained by dynamically crosslinking the fluororubber (b) in the presence of the fluororesin (A), magnesium oxide (C) and a crosslinking agent (D) under melting conditions of the fluororesin (A), wherein the magnesium oxide (C) has a 10% particle size on a volume basis of 1.0 μm or less, and the mass ratio ((A) / (B)) of the fluororesin (A) to the crosslinked fluororubber (B) is 50 / 50 to 95 / 5. Effect of the Invention

[0006] According to the present disclosure, it is possible to provide a thermoplastic polymer composition that can be produced with high productivity and has excellent flex resistance. [Brief description of the drawings]

[0007] [Figure 1] FIG. 1 is an image of a cross section of the thermoplastic polymer composition produced in Example 1. [Diagram 2] FIG. 2 is an image of a cross section of the thermoplastic polymer composition produced in Comparative Example 4. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] Specific embodiments of the present disclosure will be described in detail below, but the present disclosure is not limited to the following embodiments.

[0009] The thermoplastic polymer composition of the present disclosure contains a fluororesin (A), a crosslinked fluororubber (B), and magnesium oxide (C).

[0010] (Fluororesin (A)) The fluororesin (A) used in the present disclosure is a copolymer containing ethylene units and tetrafluoroethylene (TFE) units. The thermoplastic polymer composition of the present disclosure contains the fluororesin (A) containing ethylene units and TFE units, and therefore has excellent fuel barrier properties and moldability.

[0011] The molar ratio of ethylene units to TFE units (ethylene units / TFE units) in the above copolymer is preferably 10 / 90 or more, more preferably 15 / 85 or more, even more preferably 20 / 80 or more, and preferably 80 / 20 or less, more preferably 63 / 37 or less, even more preferably 62 / 38 or less.

[0012] The fluororesin (A) may be a copolymer of ethylene, TFE, and a monomer copolymerizable with ethylene and TFE. The copolymerizable monomer may be a monomer represented by the following formula: CH2=CX 5 Rf 3 , CF2=CFRf 3 , CF2=CFORf 3 , CH2=C(Rf 3 )2 (In the formula, X 5 is H or F, Rf 3 represents a fluoroalkyl group which may contain an ether bond. 3 , CF2=CFORf 3 and CH2=CX 5 Rf 3 Preferably, at least one selected from the group consisting of fluorine-containing vinyl monomers represented by the formula: 4 (In the formula, Rf 4 represents a perfluoroalkyl group having 1 to 5 carbon atoms. 3 is a fluoroalkyl group having 1 to 8 carbon atoms, CH2=CX 5 Rf 3More preferred is at least one selected from the group consisting of fluorine-containing vinyl monomers represented by the following formula: embedded image and further preferred is HFP. The monomer copolymerizable with ethylene and TFE may be an aliphatic unsaturated carboxylic acid such as itaconic acid or itaconic anhydride.

[0013] The content of ethylene units and TFE units in the above copolymer is preferably 90 to 100 mol %, more preferably 95 mol % or more, and even more preferably 99.9 mol % or more, based on the total monomer units of the copolymer, since a thermoplastic polymer composition can be produced with higher productivity and a thermoplastic polymer composition having better flex resistance can be obtained.

[0014] The content of monomer units copolymerizable with ethylene and TFE in the above copolymer is preferably 0 to 10 mol %, more preferably 5 mol % or less, and even more preferably 0.1 mol % or less, based on the total monomer units of the copolymer, since a thermoplastic polymer composition can be produced with higher productivity and a thermoplastic polymer composition having better flex resistance can be obtained.

[0015] The fluororesin (A) is also preferably a TFE / ethylene / HFP copolymer containing a monomer unit based on HFP (HFP unit). The TFE / ethylene / HFP copolymer preferably has a TFE / ethylene / HFP molar ratio of 40-65 / 30-60 / 0.5-20, more preferably 40-65 / 30-60 / 0.5-10.

[0016] The content of each monomer unit in the fluororesin (A) can be calculated by an appropriate combination of NMR, FT-IR, elemental analysis, and X-ray fluorescence analysis depending on the type of monomer.

[0017] The melting point of the fluororesin (A) is preferably 160°C or higher, more preferably 170°C or higher, even more preferably 180°C or higher, particularly preferably 190°C or higher, and is preferably less than 324°C, more preferably 320°C or lower, even more preferably 300°C or lower, particularly preferably 280°C or lower, and most preferably 260°C or lower, because a thermoplastic polymer composition can be produced with higher productivity and a thermoplastic polymer composition having better flex resistance can be obtained.

[0018] The melt flow rate (MFR) (297°C) of the fluororesin (A) is preferably 0.5 g / 10 min or more, more preferably 2.0 g / 10 min or more, even more preferably 5.0 g / 10 min or more, particularly preferably 8.0 g / 10 min or more, most preferably 10 g / 10 min or more, preferably 100 g / 10 min or less, more preferably 50 g / 10 min or less, even more preferably 40 g / 10 min or less, particularly preferably 35 g / 10 min or less, since the thermoplastic polymer composition can be produced with higher productivity and a thermoplastic polymer composition having better flex resistance can be obtained. The MFR of the fluororesin (A) is measured at a temperature of 297°C and a load of 5 kg.

[0019] (Crosslinked Fluorine Rubber (B)) The crosslinked fluororubber (B) contained in the thermoplastic polymer composition of the present disclosure is obtained by dynamically crosslinking the fluororubber (b) in the presence of the fluororesin (A), magnesium oxide (C) and a crosslinking agent (D) under the melting condition of the fluororesin (A). The thermoplastic polymer composition of the present disclosure contains the crosslinked fluororubber (B), and therefore has excellent fuel barrier properties and flexibility.

[0020] Dynamic crosslinking refers to dynamically crosslinking the uncrosslinked fluororubber (b) while melt-kneading it using a Banbury mixer, a pressure kneader, an extruder, etc. Using an extruder such as a twin-screw extruder for the crosslinking is preferable because it can apply a high shear force to the kneaded product.

[0021] Crosslinking under melting conditions means crosslinking the uncrosslinked fluororubber (b) at a temperature equal to or higher than the melting point of the fluororesin (A). The temperature of the crosslinking is preferably equal to or higher than the melting point of the fluororesin (A), more preferably equal to or lower than 330°C, and even more preferably equal to or lower than 320°C. The temperature of the crosslinking may be equal to or higher than 150°C as long as it is equal to or higher than the melting point of the fluororesin (A), but is preferably equal to or higher than 220°C, and more preferably equal to or higher than 240°C. By setting the temperature of the crosslinking in the above range, the fluororesin (A) and the crosslinked fluororubber (B) can be sufficiently kneaded, and at the same time, the thermal deterioration of the uncrosslinked fluororubber (b) can be suppressed.

[0022] The crosslinked fluororubber (B) can be obtained by crosslinking the uncrosslinked fluororubber (b).

[0023] In this disclosure, fluororubber is an amorphous fluoropolymer. "Amorphous" means that the magnitude of the melting peak (ΔH) that appears in the differential scanning calorimetry (DSC) (heating rate 10°C / min) or differential thermal analysis (DTA) (heating rate 10°C / min) of the fluoropolymer is 4.5 J / g or less. Fluororubber exhibits elastomeric properties by crosslinking. Elastomeric properties refer to the property that the polymer can be stretched and can retain its original length when the force required to stretch the polymer is no longer applied.

[0024] Examples of the fluororubber (b) include perfluororubber, partially fluorinated rubber, fluorine-containing thermoplastic elastomer, etc. As the fluororubber (b), partially fluorinated rubber is preferred because it allows the thermoplastic polymer composition to be produced with higher productivity and gives a thermoplastic polymer composition having better flex resistance.

[0025] In the present disclosure, the partially fluorinated rubber is a fluoropolymer that contains fluoromonomer units and has a perfluoromonomer unit content of less than 90 mol% relative to the total monomer units, has a glass transition temperature of 20°C or less, and has a melting peak (ΔH) magnitude of 4.5 J / g or less.

[0026] In the present disclosure, a perfluoromonomer is a monomer that does not contain a carbon atom-hydrogen atom bond in the molecule. The perfluoromonomer may be a monomer in which some of the fluorine atoms bonded to the carbon atom are replaced with chlorine atoms, in addition to carbon atoms and fluorine atoms, and may also have nitrogen atoms, oxygen atoms, sulfur atoms, phosphorus atoms, boron atoms, or silicon atoms in addition to carbon atoms. The perfluoromonomer is preferably a monomer in which all hydrogen atoms are replaced with fluorine atoms. The perfluoromonomer does not include a monomer that provides a crosslinking site.

[0027] Examples of the fluororubber (b) include vinylidene fluoride (VdF)-based fluororubber, tetrafluoroethylene (TFE) / propylene (Pr)-based fluororubber, tetrafluoroethylene (TFE) / propylene / vinylidene fluoride (VdF)-based fluororubber, ethylene / hexafluoropropylene (HFP)-based fluororubber, ethylene / hexafluoropropylene (HFP) / vinylidene fluoride (VdF)-based fluororubber, ethylene / hexafluoropropylene (HFP) / tetrafluoroethylene (TFE)-based fluororubber, etc. As the fluororubber (b), at least one selected from the group consisting of vinylidene fluoride-based fluororubber and tetrafluoroethylene / propylene-based fluororubber is preferable.

[0028] The vinylidene fluoride-based fluororubber is preferably a copolymer consisting of 45 to 85 mol % of vinylidene fluoride and 55 to 15 mol % of at least one other monomer copolymerizable with vinylidene fluoride, and more preferably a copolymer consisting of 50 to 80 mol % of vinylidene fluoride and 50 to 20 mol % of at least one other monomer copolymerizable with vinylidene fluoride.

[0029] At least one other monomer copolymerizable with vinylidene fluoride is, for example, tetrafluoroethylene (TFE), hexafluoropropylene (HFP), fluoroalkyl vinyl ether, chlorotrifluoroethylene (CTFE), trifluoroethylene, trifluoropropylene, pentafluoropropylene, trifluorobutene, tetrafluoroisobutene, hexafluoroisobutene, vinyl fluoride, or a monomer represented by the general formula (100): CHX 101 =CX 102 Rf 101 (In the formula, X 101 and X 102 is H on one side and F on the other side, and Rf 101 is a straight-chain or branched fluoroalkyl group having 1 to 12 carbon atoms), a fluoromonomer represented by the general formula (170): CH2=CH-(CF2) n -X 171 (In the formula, X 171 is H or F, and n is an integer of 3 to 10.) and monomers such as monomers that provide crosslinking sites; and non-fluorinated monomers such as ethylene, propylene, and alkyl vinyl ethers. These can be used alone or in any combination.

[0030] As the fluoroalkyl vinyl ether, perfluoro(methyl vinyl ether) or perfluoro(propyl vinyl ether) is preferable, and perfluoro(methyl vinyl ether) is more preferable. These can be used alone or in any combination.

[0031] The fluoromonomer represented by the general formula (100) is preferably 2,3,3,3-tetrafluoropropylene or 1,3,3,3-tetrafluoropropylene, and more preferably 2,3,3,3-tetrafluoropropylene.

[0032] As the at least one other monomer copolymerizable with vinylidene fluoride, among others, at least one selected from the group consisting of TFE, HFP, fluoroalkyl vinyl ether, CTFE, and a fluoromonomer represented by general formula (100) is preferable, and at least one selected from the group consisting of TFE, HFP, fluoroalkyl vinyl ether, and 2,3,3,3-tetrafluoropropylene is more preferable.

[0033] Specific examples of vinylidene fluoride-based fluororubbers include VdF / HFP-based rubbers, VdF / HFP / TFE-based rubbers, VdF / CTFE-based rubbers, VdF / CTFE / TFE-based rubbers, VdF / fluoromonomer-based rubbers represented by general formula (100), VdF / fluoromonomer-based rubbers represented by general formula (100) / TFE-based rubbers, VdF / perfluoro(methyl vinyl ether) [PMVE]-based rubbers, VdF / PMVE / TFE-based rubbers, VdF / PMVE / TFE / HFP-based rubbers, etc. Among these, at least one selected from the group consisting of VdF / HFP-based rubbers, VdF / HFP / TFE-based rubbers, and VdF / 2,3,3,3-tetrafluoropropylene-based rubbers is preferred, and at least one selected from the group consisting of VdF / HFP-based rubbers and VdF / HFP / TFE-based rubbers is more preferred.

[0034] The VdF / HFP rubber preferably has a VdF / HFP molar ratio of 45-85 / 55-15, more preferably 50-80 / 50-20, and further preferably 60-80 / 40-20.

[0035] The VdF / HFP / TFE rubber preferably has a molar ratio of VdF / HFP / TFE of 40-80 / 10-35 / 10-35.

[0036] The VdF / 2,3,3,3-tetrafluoropropylene rubber preferably has a VdF / 2,3,3,3-tetrafluoropropylene molar ratio of 45-85 / 55-15, more preferably 50-80 / 50-20, and further preferably 60-80 / 40-20.

[0037] The above-mentioned tetrafluoroethylene / propylene-based fluororubber is preferably a copolymer consisting of 45 to 70 mol % of tetrafluoroethylene, 55 to 30 mol % of propylene, and 0 to 5 mol % of a fluoromonomer that provides a crosslinking site.

[0038] The content of each monomer unit in the above-mentioned fluororubber (b) can be calculated by an appropriate combination of NMR, FT-IR, elemental analysis, and X-ray fluorescence analysis depending on the type of monomer.

[0039] The fluororubber (b) is also preferably made of a copolymer containing a monomer unit derived from a monomer that provides a crosslinking site. Examples of the monomer that provides a crosslinking site include iodine-containing monomers such as perfluoro(6,6-dihydro-6-iodo-3-oxa-1-hexene) and perfluoro(5-iodo-3-oxa-1-pentene) as described in JP-B-5-63482 and JP-A-7-316234, bromine-containing monomers as described in JP-T-4-505341, cyano-containing monomers, carboxyl-containing monomers, and alkoxycarbonyl-containing monomers as described in JP-T-4-505345 and JP-T-5-500070.

[0040] The fluororubber (b) may be one obtained by using a chain transfer agent during polymerization. A bromine compound or an iodine compound may be used as the chain transfer agent. An example of a polymerization method using a bromine compound or an iodine compound is a method in which emulsion polymerization is carried out in an aqueous medium under pressure in the presence of a bromine compound or an iodine compound in a substantially oxygen-free state (iodine transfer polymerization method). Representative examples of the bromine compound or iodine compound to be used include, for example, compounds represented by the general formula: R2 I x Br y (In the formula, x and y are each an integer of 0 to 2, and 1≦x+y≦2 is satisfied; R 2 is a saturated or unsaturated fluorohydrocarbon group or chlorofluorohydrocarbon group having 1 to 16 carbon atoms, or a hydrocarbon group having 1 to 3 carbon atoms, which may contain an oxygen atom). By using a bromine compound or an iodine compound, iodine or bromine is introduced into the polymer and functions as a crosslinking point.

[0041] The fluorine content of the fluororubber (b) is preferably 55 to 73 mass%, more preferably 61 mass% or more, even more preferably 63 mass% or more, still more preferably 65 mass% or more, particularly preferably 67 mass% or more, most preferably 69 mass% or more, and more preferably less than 71 mass%. 19 It can be calculated from the composition of the fluororubber measured by F-NMR.

[0042] The Mooney viscosity at 100°C (ML1+10(100°C)) of the fluororubber (b) is preferably 2 or more, more preferably 5 or more, and even more preferably 10 or more, because a thermoplastic polymer composition can be produced with higher productivity and a thermoplastic polymer composition having better flex resistance can be obtained. Also, it is preferably 200 or less, more preferably 120 or less, and even more preferably 100 or less. The Mooney viscosity is a value measured in accordance with ASTM-D1646-15 and JIS K6300-1:2013.

[0043] (Magnesium oxide (C)) The thermoplastic polymer composition of the present disclosure contains magnesium oxide (C). The magnesium oxide (C) has a 10% volumetric particle size of 1.0 μm or less. Since the thermoplastic polymer composition of the present disclosure contains magnesium oxide having such a small particle size, it can be produced with high productivity and has excellent flex resistance.

[0044] As shown in the image of Figure 1 described later, by using magnesium oxide (C) with a 10% particle size on a volume basis of 1.0 μm or less, it was found that when the magnesium oxide (C) is kneaded with the fluororesin (A) and the fluororubber (b), the aggregation of the magnesium oxide (C) particles can be suppressed, and therefore the magnesium oxide (C) can be highly dispersed in the composition. As a result, it is presumed that there are almost no aggregates that are the starting point for crack generation in the finally obtained thermoplastic polymer composition, and the flex resistance is improved.

[0045] The 10% particle size on a volume basis of magnesium oxide (C) is 1.0 μm or less, which allows the production of a thermoplastic polymer composition with higher productivity and gives a thermoplastic polymer composition having better flex resistance, and is therefore preferably 0.8 μm or less, more preferably 0.6 μm or less, even more preferably 0.4 μm or less, and preferably 0.1 μm or more.

[0046] The 50% particle size on a volume basis of the magnesium oxide (C) is preferably 2.0 μm or less, more preferably 1.5 μm or less, even more preferably 1.0 μm or less, and preferably 0.1 μm or more, since a thermoplastic polymer composition can be produced with higher productivity and a thermoplastic polymer composition having better flex resistance can be obtained.

[0047] The 90% particle size on a volume basis of the magnesium oxide (C) is preferably 5.0 μm or less, more preferably 2.5 μm or less, even more preferably 1.5 μm or less, and preferably 0.1 μm or more, since a thermoplastic polymer composition can be produced with higher productivity and a thermoplastic polymer composition having better flex resistance can be obtained.

[0048] The 10% particle size of magnesium oxide (C) is the cumulative 10% particle size based on volume, and can be measured by laser diffraction and scattering. The 50% particle size of magnesium oxide (C) is the cumulative 50% particle size based on volume, and can be measured by laser diffraction and scattering. The 90% particle size of magnesium oxide (C) is the cumulative 90% particle size based on volume, and can be measured by laser diffraction and scattering.

[0049] The purity of magnesium oxide (C) is preferably 99.0 mass% or more. When the purity of magnesium oxide (C) is within the above range, the degree of crosslinking of the crosslinked fluororubber (B) is further improved. The purity of magnesium oxide (C) can be measured, for example, by ICP emission spectrometry.

[0050] The content of magnesium oxide (C) is preferably 0.01 to 10 parts by mass, more preferably 1.0 part by mass or more, even more preferably 2.0 parts by mass or more, more preferably 9.0 parts by mass or less, even more preferably 8.0 parts by mass or less, and particularly preferably 7.0 parts by mass or less, relative to 100 parts by mass of the fluororubber (b), because the thermoplastic polymer composition can be produced with higher productivity and a thermoplastic polymer composition having better flex resistance can be obtained.

[0051] (Crosslinking agent (D)) In the present disclosure, a crosslinking agent (D) is used to obtain the crosslinked fluororubber (B). Examples of the crosslinking agent include crosslinking agents that are commonly used in polyol crosslinking, polyamine crosslinking, and peroxide crosslinking. The crosslinking agent is preferably at least one selected from the group consisting of polyhydroxy compounds, polyamine compounds, and peroxides, and more preferably a polyhydroxy compound.

[0052] Examples of the polyamine compound include hexamethylenediamine carbamate, N,N'-dicinnamylidene-1,6-hexamethylenediamine, 4,4'-bis(aminocyclohexyl)methane carbamate, etc. Among these, N,N'-dicinnamylidene-1,6-hexamethylenediamine is preferred.

[0053] The content of the polyamine compound is preferably from 0.05 to 10 parts by mass, and more preferably from 0.5 to 5 parts by mass, based on 100 parts by mass of the fluororubber (b).

[0054] As the polyhydroxy compound, polyhydroxy aromatic compounds are preferably used because of their excellent heat resistance. The polyhydroxy aromatic compounds are not particularly limited, and examples thereof include 2,2-bis(4-hydroxyphenyl)propane (hereinafter referred to as bisphenol A), 2,2-bis(4-hydroxyphenyl)perfluoropropane (hereinafter referred to as bisphenol AF), resorcin, 1,3-dihydroxybenzene, 1,7-dihydroxynaphthalene, 2,7-dihydroxynaphthalene, 2,6-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 4,4'-dihydroxydiphenyl, 4,4'-dihydroxystilbene, 2,6- Examples include dihydroxyanthracene, hydroquinone, catechol, 2,2-bis(4-hydroxyphenyl)butane (hereinafter referred to as bisphenol B), 4,4-bis(4-hydroxyphenyl)valeric acid, 2,2-bis(4-hydroxyphenyl)tetrafluorodichloropropane, 4,4'-dihydroxydiphenyl sulfone, 4,4'-dihydroxydiphenyl ketone, tri(4-hydroxyphenyl)methane, 3,3',5,5'-tetrachlorobisphenol A, and 3,3',5,5'-tetrabromobisphenol A. Among these, bisphenol AF is preferred.

[0055] The content of the polyhydroxy compound is preferably from 0.05 to 10 parts by mass, and more preferably from 0.5 to 5 parts by mass, based on 100 parts by mass of the fluororubber (b).

[0056] When the crosslinking agent is a polyhydroxy compound, the crosslinked fluororubber (B) is preferably one obtained by dynamically crosslinking the fluororubber (b) under the melting condition of the fluororesin (A) in the presence of a crosslinking accelerator in addition to the fluororesin (A), magnesium oxide (C) and crosslinking agent (D). The crosslinking accelerator promotes the formation of intramolecular double bonds in the defluorination reaction of the polymer main chain and the addition of the polyhydroxy compound to the double bonds thus formed.

[0057] The crosslinking accelerator may be an onium compound. Among the onium compounds, at least one selected from the group consisting of ammonium compounds such as quaternary ammonium salts, phosphonium compounds such as quaternary phosphonium salts, oxonium compounds, sulfonium compounds, cyclic amines, and monofunctional amine compounds is preferred, and at least one selected from the group consisting of quaternary ammonium salts and quaternary phosphonium salts is more preferred.

[0058] The quaternary ammonium salt is not particularly limited, and examples thereof include 8-methyl-1,8-diazabicyclo[5.4.0]-7-undecenium chloride, 8-methyl-1,8-diazabicyclo[5.4.0]-7-undecenium iodide, 8-methyl-1,8-diazabicyclo[5.4.0]-7-undecenium hydroxide, 8-methyl-1,8-diazabicyclo[5.4.0]-7-undecenium methyl sulfate, 8-ethyl-1,8-diazabicyclo[5.4.0]-7-undecenium bromide, 8-propyl-1,8-diazabicyclo[5.4.0]-7-undecenium bromide, 8-dodecyl-1,8-diazabicyclo[5.4.0]-7-undecenium chloride, 8-dodecyl Examples of the DBU-B include 8-benzyl-1,8-diazabicyclo[5.4.0]-7-undecenium hydroxide, 8-eicosyl-1,8-diazabicyclo[5.4.0]-7-undecenium chloride, 8-tetracosyl-1,8-diazabicyclo[5.4.0]-7-undecenium chloride, 8-benzyl-1,8-diazabicyclo[5.4.0]-7-undecenium chloride (hereinafter referred to as DBU-B), 8-benzyl-1,8-diazabicyclo[5.4.0]-7-undecenium hydroxide, 8-phenethyl-1,8-diazabicyclo[5.4.0]-7-undecenium chloride, and 8-(3-phenylpropyl)-1,8-diazabicyclo[5.4.0]-7-undecenium chloride. Among these, DBU-B is preferred because of its excellent crosslinkability and various physical properties.

[0059] The quaternary phosphonium salt is not particularly limited, and examples thereof include tetrabutyl phosphonium chloride, benzyl triphenyl phosphonium chloride (hereinafter referred to as BTPPC), benzyl trimethyl phosphonium chloride, benzyl tributyl phosphonium chloride, tributyl allyl phosphonium chloride, tributyl-2-methoxypropyl phosphonium chloride, and benzyl phenyl (dimethylamino) phosphonium chloride. Among these, benzyl triphenyl phosphonium chloride (BTPPC) is preferred because of its excellent crosslinkability and various physical properties.

[0060] The content of the crosslinking accelerator is not particularly limited, but is preferably from 0.05 to 5 parts by mass, and more preferably from 0.1 to 1 part by mass, per 100 parts by mass of the fluororubber (b).

[0061] In addition, a solid solution (containing no chlorine atoms) of bisphenol AF and benzyltriphenylphosphonium is used as the crosslinking agent and crosslinking accelerator in a preferred embodiment. The mass ratio of benzyltriphenylphosphonium to bisphenol AF in the solid solution is preferably 1:2 to 1:4, taking into consideration the dispersibility of the solid solution in the composition.

[0062] The content of the solid solution (for example, a solid solution of benzyltriphenylphosphonium and bisphenol AF in a mass ratio of 1:4) is preferably 0.1 to 2.0 parts by mass per 100 parts by mass of the fluororubber (b), taking into consideration crosslinkability and dispersibility.

[0063] The peroxide is not particularly limited as long as it is a crosslinking agent that is usually used for peroxide crosslinking, and generally, it is preferable to use one that easily generates peroxy radicals in the presence of heat or an oxidation-reduction system.Specific examples include 1,1-bis(t-butylperoxy)-3,5,5-trimethylcyclohexane, 2,5-dimethylhexane-2,5-dihydroperoxide, di-t-butyl peroxide, t-butylcumyl peroxide, dicumyl peroxide, α,α'-bis(t-butylperoxy)-p-diisopropylbenzene, 2,5-dimethyl-2,5-bis(t-butylperoxy)hexane, 2,5-dimethyl-2,5-bis(t-butylperoxy)-hexyne-3, benzoyl peroxide, t-butylperoxybenzene, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, t-butylperoxymaleic acid, t-butylperoxyisopropyl carbonate, and t-butylperoxybenzoate. Among these, 2,5-dimethyl-2,5-bis(t-butylperoxy)hexane and 2,5-dimethyl-2,5-bis(t-butylperoxy)-hexyne-3 are preferred.

[0064] The content of the peroxide is preferably from 0.05 to 10 parts by mass, and more preferably from 1.0 to 5 parts by mass, based on 100 parts by mass of the fluororubber (b).

[0065] When the crosslinking agent is a peroxide, the crosslinked fluororubber (B) is preferably obtained by dynamically crosslinking the fluororubber (b) under melting conditions of the fluororesin (A) in the presence of a polyfunctional crosslinking aid in addition to the fluororesin (A), magnesium oxide (C) and crosslinking agent (D).

[0066] Multifunctional crosslinking aids include triallyl cyanurate, trimethallyl isocyanurate, triallyl isocyanurate (TAIC), triacryl formal, triallyl trimellitate, N,N'-m-phenylene bismaleimide, dipropargyl terephthalate, diallyl phthalate, tetraallyl terephthalate amide, triallyl phosphate, bismaleimide, fluorinated triallyl isocyanurate (1,3,5-tris(2,3,3-trifluoro-2-propenyl)-1,3,5-triaryl terephthalate, tetraaryl terephthalate amide, triallyl phosphate, bismaleimide, fluorinated triallyl isocyanurate (1,3,5-tris(2,3,3-trifluoro-2-propenyl)-1,3,5-triaryl terephthalate, tetraaryl terephthalate amide, tri ... Examples of the fluororubber include tris(diallylamine)-S-triazine, triallyl phosphite, N,N-diallylacrylamide, 1,6-divinyldodecafluorohexane, hexaallyl phosphoramide, N,N,N',N'-tetraallylphthalamide, N,N,N',N'-tetraallylmalonamide, trivinyl isocyanurate, 2,4,6-trivinylmethyltrisiloxane, tri(5-norbornene-2-methylene) cyanurate, and triallyl phosphite. Among these, triallyl isocyanurate (TAIC) is preferred. When kneading the fluororubber and the polyfunctional crosslinking aid, the polyfunctional crosslinking aid may be impregnated into an inactive inorganic powder or the like.

[0067] The content of the polyfunctional crosslinking aid is preferably from 0.1 to 10 parts by mass, and more preferably from 0.5 to 5 parts by mass, based on 100 parts by mass of the fluororubber (b).

[0068] (Acid acceptor (excluding magnesium oxide)) The thermoplastic polymer composition of the present disclosure may contain an acid acceptor other than magnesium oxide. Examples of the acid acceptor (excluding magnesium oxide) include magnesium hydroxide, barium hydroxide, magnesium carbonate, barium carbonate, quicklime, slaked lime, calcium hydroxide, calcium carbonate, calcium silicate, calcium stearate, zinc stearate, calcium phthalate, calcium phosphite, tin oxide, and basic tin phosphite.

[0069] The amount of the acid acceptor is preferably 0.01 to 10 parts by mass, more preferably 0.1 to 8 parts by mass, and further preferably 0.5 to 6 parts by mass, based on 100 parts by mass of the fluororubber (b).

[0070] (Thermoplastic polymer composition) The thermoplastic polymer composition of the present disclosure contains a fluororesin (A), a crosslinked fluororubber (B), and magnesium oxide (C).

[0071] The mass ratio ((A) / (B)) of the fluororesin (A) to the crosslinked fluororubber (B) is 50 / 50 to 95 / 5, preferably 55 / 45 or more, more preferably 60 / 40 or more, and preferably 90 / 10 or less, more preferably 85 / 15 or less. By setting the mass ratio of the fluororesin (A) to the crosslinked fluororubber (B) within the above range, the thermoplastic polymer composition can be produced with high productivity, and a thermoplastic polymer composition having excellent flex resistance can be obtained.

[0072] In the thermoplastic polymer composition of the present disclosure, the fluororesin (A) may form a continuous phase and the crosslinked fluororubber (B) may form a dispersed phase, or the fluororesin (A) and the crosslinked fluororubber (B) may form a co-continuous phase structure, but it is preferable that the fluororesin (A) forms a continuous phase and the crosslinked fluororubber (B) forms a dispersed phase. Also, a co-continuous phase structure of the fluororesin (A) and the crosslinked fluororubber (B) may be included in a part of the structure in which the fluororesin (A) forms a continuous phase and the crosslinked fluororubber (B) forms a dispersed phase.

[0073] Even if uncrosslinked fluororubber (b) forms a matrix initially when dispersed, when the uncrosslinked fluororubber (b) changes to crosslinked fluororubber (B) through a crosslinking reaction, the crosslinked fluororubber (B) has a higher melt viscosity than the uncrosslinked fluororubber (b), so the crosslinked fluororubber (B) will form a dispersed phase, or the fluororesin (A) and crosslinked fluororubber (B) will form a co-continuous phase structure.

[0074] The MFR (297°C) of the thermoplastic polymer composition of the present disclosure is preferably 0.5 g / 10 min or more, more preferably 1.0 g / 10 min or more, even more preferably 5.0 g / 10 min or more, particularly preferably 8 g / 10 min or more, most preferably 10 g / 10 min or more, preferably 100 g / 10 min or less, more preferably 50 g / 10 min or less, even more preferably 40 g / 10 min or less, particularly preferably 30 g / 10 min or less. The MFR of the thermoplastic polymer composition is measured at a temperature of 297°C and a load of 5 kg.

[0075] The thermoplastic polymer composition of the present disclosure has a feature of exhibiting a high MIT value. In one embodiment, the thermoplastic polymer composition of the present disclosure exhibits an MIT value 1.2 times or more higher than the MIT value of a thermoplastic polymer composition having the same components except that it contains magnesium oxide having a 10% volumetric particle size of 1.99 μm instead of magnesium oxide (C). The MIT value can be measured by the measurement method described in the Examples. When calculating the magnification of the MIT value, not only the composition of the thermoplastic polymer composition other than the 10% volumetric particle size of magnesium oxide is the same, but also the preparation method for preparing a test piece from the thermoplastic polymer composition is the same. For example, when a test piece is prepared by molding an arbitrary thermoplastic polymer composition under specified conditions using an extrusion molding method, a test piece is prepared by molding a thermoplastic polymer composition containing magnesium oxide having a 10% volumetric particle size of 1.99 μm using an extrusion molding method under the same conditions.

[0076] The shape of the thermoplastic polymer composition of the present disclosure is not particularly limited and may be in the form of powder, pellets, crumbs, etc., but is preferably in the form of pellets since it can be produced with high productivity.

[0077] The thermoplastic polymer composition of the present disclosure also preferably has electrical conductivity in order to prevent ignition due to accumulation of static charge. From this viewpoint, the thermoplastic polymer composition of the present disclosure preferably contains a conductive material such as carbon black or acetylene black. The content of the conductive material is preferably 0.01 to 20 mass%, more preferably 1 to 18 mass%, and even more preferably 5 to 15 mass% relative to the thermoplastic polymer composition of the present disclosure.

[0078] In addition, other polymers such as polyethylene, polypropylene, polyamide, polyester, and polyurethane, inorganic fillers such as talc, celite, clay, titanium oxide, carbon black, and barium sulfate, pigments, flame retardants, lubricants, light stabilizers, weather stabilizers, antistatic agents, ultraviolet absorbers, antioxidants, release agents, foaming agents, fragrances, oils, and softeners can be added to the thermoplastic polymer composition of the present disclosure, as long as the addition does not affect the intended effects.

[0079] (Manufacturing method) The thermoplastic polymer composition of the present disclosure can be produced by kneading a fluororubber composition containing a fluororesin (A), a fluororubber (b), magnesium oxide (C) and a crosslinking agent (D) at a temperature equal to or higher than the melting point of the fluororesin (A).

[0080] The thermoplastic polymer composition of the present disclosure can be suitably produced by a production method in which a fluororubber composition containing a fluororesin (A), a fluororubber (b), magnesium oxide (C) and a crosslinking agent (D) is kneaded in a cylinder using an extruder equipped with a cylinder and a die at a temperature equal to or higher than the melting point of the fluororesin (A), and the kneaded mixture obtained is extruded through a die to obtain pellets of the thermoplastic polymer composition. The thermoplastic polymer composition of the present disclosure can be produced by such a production method, and as described below, the extrusion pressure is unlikely to increase when produced by such a production method, so that the composition can be produced with high productivity.

[0081] In the above-mentioned production method, the fluororubber (b) is dynamically crosslinked when the fluororubber composition is kneaded, and a thermoplastic polymer composition containing the fluororesin (A) and the crosslinked fluororubber (B) can be obtained.

[0082] In the above-mentioned production method, the fluororubber (b), the crosslinking agent (D) and the crosslinking accelerator are kneaded to prepare a fluororubber compound, and then the compound, the fluororubber composition containing the fluororesin (A) and magnesium oxide (C) are kneaded at a temperature equal to or higher than the melting point of the fluororesin (A), and the obtained kneaded product may be extruded through a die.

[0083] For the kneading, a Banbury mixer, a pressure kneader, an extruder, or the like can be used.

[0084] The manufacturing method of the present disclosure can be characterized in that, when the kneaded material is continuously extruded from the die for 60 minutes, the rate of change in pressure calculated by the following formula is 5% or less. Rate of change of pressure (%) = (X 60 -X0) / X0 X0: Pressure (MPa) applied to the kneaded material in the die at the start of extrusion X 60 : Pressure (MPa) applied to the kneaded material in the die 60 minutes after the start of extrusion

[0085] The production method of the present disclosure uses magnesium oxide (C) having a particle size within the above range, and therefore the extrusion pressure is unlikely to increase even if the kneaded material is continuously extruded from the die for a long period of time, and therefore the thermoplastic polymer composition (pellets) can be produced with high productivity.

[0086] (molded product) The molded article of the present disclosure can be obtained by molding the above-mentioned thermoplastic polymer composition. The shape of the molded article is not particularly limited, and examples thereof include a tube, a hose, a sheet, and a film.

[0087] The molded product can be produced by using a general molding method and molding apparatus, etc. As the molding method, any method such as injection molding, extrusion molding, compression molding, blow molding, calendar molding, vacuum molding, etc. can be used.

[0088] The molded article of the present disclosure can form, for example, a layer of a laminate. The laminate can include a layer made of the molded article of the present disclosure and a layer made of another material. Examples of the other material include fluororesin, non-fluororesin, fluororubber, non-fluororubber, etc.

[0089] Examples of fluororesins include tetrafluoroethylene (TFE) / perfluoro(alkyl vinyl ether) (PAVE) copolymers, tetrafluoroethylene (TFE) / hexafluoropropylene (HFP) copolymers, TFE / ethylene copolymers (ETFE), TFE / ethylene / HFP copolymers, chlorotrifluoroethylene (CTFE) / ethylene copolymers (ECTFE), polyvinylidene fluoride (PVdF), polychlorotrifluoroethylene (PCTFE), CTFE / TFE copolymers, TFE / vinylidene fluoride (VdF) copolymers (VT), polyvinyl fluoride (PVF), TFE / VdF / CTFE copolymers (VTC), and TFE / HFP / VdF copolymers.

[0090] Examples of non-fluorinated resins include polyamide resin, polyolefin resin, vinyl chloride resin, polyurethane resin, polyester resin, polyaramid resin, polyimide resin, polyamideimide resin, polyphenylene oxide resin, polyacetal resin, polycarbonate resin, acrylic resin, styrene resin, acrylonitrile / butadiene / styrene resin (ABS), cellulose resin, polyether ether ketone resin (PEEK), polysulfone resin, polyethersulfone resin (PES), polyetherimide resin, ethylene / vinyl alcohol copolymer resin, polyphenylene sulfide resin, polybutylene naphthalate resin, polybutylene terephthalate resin, and polyphthalamide (PPA).

[0091] Examples of fluororubber include vinylidene fluoride (VdF)-based fluororubber, tetrafluoroethylene (TFE) / propylene (Pr)-based fluororubber, tetrafluoroethylene (TFE) / propylene / vinylidene fluoride (VdF)-based fluororubber, ethylene / hexafluoropropylene (HFP)-based fluororubber, ethylene / hexafluoropropylene (HFP) / vinylidene fluoride (VdF)-based fluororubber, and ethylene / hexafluoropropylene (HFP) / tetrafluoroethylene (TFE)-based fluororubber.

[0092] Examples of non-fluorinated rubbers include acrylonitrile-butadiene rubber, hydrogenated acrylonitrile-butadiene rubber, blended rubber of acrylonitrile-butadiene rubber and polyvinyl chloride, blended rubber of acrylonitrile-butadiene rubber and acrylic rubber, chlorinated polyethylene, fluorinated rubber, epichlorohydrin rubber, ethylene-propylene rubber, chlorosulfonated polyethylene rubber, acrylic rubber, silicone rubber, butyl rubber, styrene-butadiene rubber, ethylene-vinyl acetate copolymer, α,β-unsaturated nitrile-conjugated diene copolymer rubber, and hydrogenated α,β-unsaturated nitrile-conjugated diene copolymer rubber.

[0093] The thermoplastic polymer composition, molded article, and laminate of the present disclosure have excellent fuel barrier properties and flex resistance, and therefore can be used in a variety of applications.

[0094] For example, they have suitable properties for use in seals, bellows, diaphragms, hoses, tubes, electric wires, etc., such as gaskets and non-contact and contact type packings (self-sealing packings, piston rings, split ring type packings, mechanical seals, oil seals, etc.), which require heat resistance, oil resistance, fuel oil resistance, LLC resistance, and steam resistance and are used in the engine body, main motion system, valve train, lubrication / cooling system, fuel system, intake / exhaust system, etc. of automobile engines, transmission system of drivetrain, steering system, brake system, etc. of chassis, basic electrical components of electrical equipment, electrical components of control systems, electrical components of equipment, etc.

[0095] Specifically, it can be used for the applications listed below.

[0096] Gaskets for the engine body, such as cylinder head gaskets, cylinder head cover gaskets, oil pan packings, general gaskets, O-rings, packings, seals such as timing belt cover gaskets, hoses such as control hoses, vibration-proof rubber for engine mounts, sealing materials for high-pressure valves in hydrogen storage systems, etc.

[0097] Shaft seals such as crankshaft seals and camshaft seals for the main moving system.

[0098] Valve stem seals for engine valves, etc.

[0099] For lubrication and cooling systems, engine oil cooler hoses, oil return hoses, seal gaskets, etc. for the engine oil cooler, water hoses around the radiator, vacuum pump oil hoses for the vacuum pump, etc.

[0100] Fuel system fuel hoses, fuel tubes, fuel sealants, and other fuel system components. Fuel hoses or fuel tubes include fuel hoses such as filler (neck) hoses, fuel supply hoses, fuel return hoses, vapor (evaporation) hoses, in-tank hoses for fuel tanks, fuel piping tubes, and carburetor control hoses. Fuel sealants include fuel pump oil seals, fuel tank fuel sender seals, filler seals, tank packing, and other fuel piping tube connector O-rings, injector cushion rings, injector seal rings, injector O-rings, and carburetor flange gaskets. Other fuel system components include fuel pump diaphragms and valves, in-tank fuel pump mounts, pressure regulator diaphragms and check valves for fuel injection devices, carburetor needle valve petals, acceleration pump pistons, and valve seats and diaphragms for composite air control devices (CAC). Among these, the material is suitable for use as a fuel hose or fuel tube, particularly as a filler neck hose or a fuel supply hose, and is also suitable as a fuel seal, particularly as a fuel sender seal.

[0101] For intake and exhaust systems, intake manifold packing, exhaust manifold packing, etc., EGR (exhaust gas recirculation) diaphragms, control hoses, emission control hoses, etc., BPT diaphragms, AB valve afterburn prevention valve seats, etc., throttle body packing, turbocharger turbo oil hose (supply), turbo oil hose (return), turbo air hose, intercooler hose, turbine shaft seals, etc.

[0102] Transmission-related items include bearing seals, oil seals, O-rings, packing, torque converter hoses, etc., as well as AT transmission oil hoses, ATF hoses, O-rings, packing, etc.

[0103] Steering system, power steering oil hose, etc.

[0104] Brake system oil seals, O-rings, gaskets, brake oil hoses, master bag air valves, vacuum valves, diaphragms, master cylinder piston cups (rubber cups), caliper seals, boots, etc.

[0105] Basic electrical components such as insulators and sheaths for electrical wires (harnesses), and tubes for exterior harness components.

[0106] Coating materials for various sensor wires in electrical control system components, etc.

[0107] Electrical parts such as O-rings, packing, and cooler hoses for car air conditioners, and exterior parts such as wiper blades.

[0108] In addition to automobiles, the material is also suitable for applications such as oil-resistant, chemical-resistant, heat-resistant, steam-resistant, or weather-resistant packing, O-rings, hoses, other sealing materials, diaphragms, and valves in transportation means such as ships and aircraft, similar packing, O-rings, sealing materials, diaphragms, valves, hoses, rolls, tubes, chemical-resistant coatings, and linings in chemical plants, similar packing, O-rings, hoses, sealing materials, belts, diaphragms, valves, rolls, and tubes in food plant equipment and food equipment (including household products), similar packing, O-rings, hoses, sealing materials, diaphragms, valves, and tubes in nuclear plant equipment, and similar packing, O-rings, hoses, sealing materials, diaphragms, valves, rolls, tubes, linings, mandrels, electric wires, flexible joints, belts, rubber sheets, weather strips, and roll blades in PPC copiers in general industrial parts.

[0109] In addition, in the case of food rubber sealant applications, there are problems with conventional rubber sealants, such as flavoring and rubber fragments being mixed into food, but by using the molded product of the present disclosure, this problem can be improved and the molded product of the present disclosure can be used favorably. Since it has chemical resistance, low elution and low flavoring, in the medical and chemical fields, it can be applied to oil-resistant, chemical-resistant, heat-resistant, steam-resistant or weather-resistant sealants, lid materials, belts, rolls, hoses, tubes, films, coatings, linings, joints, containers, etc. In the general industrial field, it can be used favorably for rubber rolls, O-rings, packings, sealing materials, etc., for the purpose of improving the strength, slipperiness, chemical resistance, and permeability of rubber materials. In particular, it can be used favorably for packing applications for lithium ion batteries, since it can maintain both chemical resistance and sealing at the same time. In addition, it can be used favorably in applications where low friction slidability is required.

[0110] Among these, the thermoplastic polymer composition, molded article, and laminate of the present disclosure can be suitably used as a hose for transporting fluids, such as hydrogen, refrigerants for air conditioners, inert gases, fuels, oils, and water.

[0111] The thermoplastic polymer composition, molded article, and laminate of the present disclosure are preferably used as a fuel hose or fuel tube, and particularly preferably as a filler neck hose or fuel supply hose. That is, the molded article and laminate are preferably a fuel hose or fuel tube, and particularly preferably a filler neck hose or fuel supply hose.

[0112] Although the embodiments have been described above, it will be understood that various changes in form and details are possible without departing from the spirit and scope of the claims.

[0113] <1> According to a first aspect of the present disclosure, A thermoplastic polymer composition comprising a fluororesin (A), a crosslinked fluororubber (B) and magnesium oxide (C), The fluororesin (A) is a copolymer containing ethylene units and tetrafluoroethylene units, The crosslinked fluororubber (B) is obtained by dynamically crosslinking the fluororubber (b) in the presence of the fluororesin (A), magnesium oxide (C) and a crosslinking agent (D) under the melting condition of the fluororesin (A), The magnesium oxide (C) has a volume-based 10% particle size of 1.0 μm or less, The mass ratio ((A) / (B)) of the fluororesin (A) to the crosslinked fluororubber (B) is 50 / 50 to 95 / 5. A thermoplastic polymer composition is provided. <2> According to a second aspect of the present disclosure, There is provided a thermoplastic polymer composition according to a first aspect, in which the magnesium oxide (C) has a 50% volumetric particle size of 1.0 μm or less. <3> According to a third aspect of the present disclosure, There is provided a thermoplastic polymer composition according to the first or second aspect, wherein the content of magnesium oxide (C) is 0.01 to 10 parts by mass per 100 parts by mass of the fluororubber (b). <4> According to a fourth aspect of the present disclosure, There is provided a thermoplastic polymer composition according to any one of the first to third aspects, in which the fluororesin (A) has a melting point of 160 to 320°C. <5> According to a fifth aspect of the present disclosure, There is provided a thermoplastic polymer composition according to any one of the first to fourth aspects, in which the fluororubber (b) is a partially fluorinated rubber. <6> According to a sixth aspect of the present disclosure, There is provided a thermoplastic polymer composition according to any one of the first to fifth aspects, wherein the fluororubber (b) is at least one selected from the group consisting of vinylidene fluoride / hexafluoropropylene-based fluororubbers, vinylidene fluoride / tetrafluoroethylene / hexafluoropropylene-based fluororubbers, and tetrafluoroethylene / propylene-based fluororubbers. <7> According to a seventh aspect of the present disclosure, According to any one of the first to sixth aspects, there is provided a thermoplastic polymer composition, wherein the crosslinking agent (D) is at least one selected from the group consisting of polyhydroxy compounds, polyamine compounds and peroxides. <8> According to an eighth aspect of the present disclosure, There is provided a thermoplastic polymer composition according to any of the first to seventh aspects, which exhibits an MIT value that is 1.2 times or more the MIT value of a thermoplastic polymer composition having the same components except that it contains magnesium oxide having a 10% particle size on a volume basis of 1.99 μm instead of magnesium oxide (C). <9> According to a ninth aspect of the present disclosure, the fluororesin (A) is a copolymer having a molar ratio of ethylene units and tetrafluoroethylene units (ethylene units / TFE units) of 10 / 90 to 62 / 38 and a content of ethylene units and tetrafluoroethylene units of 90 to 100 mol % based on the total monomer units; the fluororubber (b) is a vinylidene fluoride / hexafluoropropylene-based rubber having a molar ratio of vinylidene fluoride / hexafluoropropylene of 45-85 / 55-15, or a vinylidene fluoride / tetrafluoroethylene / hexafluoropropylene-based fluororubber having a molar ratio of vinylidene fluoride / tetrafluoroethylene / hexafluoropropylene of 40-80 / 10-35 / 10-35, The magnesium oxide (C) has a volume-based 10% particle size of 0.1 to 0.4 μm; The crosslinking agent (D) is a polyhydroxy compound; a mass ratio ((A) / (B)) of the fluororesin (A) to the crosslinked fluororubber (B) is 60 / 40 to 85 / 15; The melt flow rate (297°C) of the thermoplastic polymer composition is 1.0 to 30 g / 10 min. According to any one of the first to eighth aspects, there is provided a thermoplastic polymer composition. <10> According to a tenth aspect of the present disclosure, There is provided a thermoplastic polymer composition according to any one of the first to ninth aspects which is in the form of pellets. <11> According to an eleventh aspect of the present disclosure, There is provided a molded article obtainable by molding the thermoplastic polymer composition according to any one of the first to tenth aspects. <12> According to a twelfth aspect of the present disclosure, According to an eleventh aspect there is provided a moulded article which is a tube or hose. <13> According to a thirteenth aspect of the present disclosure, A method for producing a thermoplastic polymer composition according to any one of the first to tenth aspects, The present invention provides a production method for obtaining pellets of a thermoplastic polymer composition by kneading a fluororubber composition containing a fluororesin (A), a fluororubber (b), magnesium oxide (C) and a crosslinking agent (D) in an extruder equipped with a cylinder and a die at a temperature equal to or higher than the melting point of the fluororesin (A) in the cylinder and extruding the resulting kneaded mixture through the die. <14> According to a fourteenth aspect of the present disclosure, There is provided a production method according to a thirteenth aspect, in which, when the kneaded material is continuously extruded from the die for 60 minutes, a rate of change in pressure calculated by the following formula is 5% or less. Rate of change of pressure (%) = (X 60 -X0) / X0 X0: Pressure (MPa) applied to the kneaded material in the die at the start of extrusion X 60 : Pressure (MPa) applied to the kneaded material in the die 60 minutes after the start of extrusion EXAMPLES

[0114] Next, embodiments of the present disclosure will be described with reference to examples, but the present disclosure is not limited to these examples.

[0115] The values ​​in the examples were measured by the following methods.

[0116] Monomer Composition 19 It was measured by F-NMR analysis.

[0117] Melting point Using a differential scanning calorimeter [DSC], the melting peak was recorded when the temperature was raised at a rate of 10° C. / min, and the temperature corresponding to the maximum value was taken as the melting point.

[0118] Melt Flow Rate (MFR) Using a melt indexer (manufactured by Toyo Seiki Seisakusho), the mass (g) of polymer flowing out per unit time (10 minutes) from a nozzle with a diameter of 2 mm and a length of 8 mm under a load of 5 kg at 297°C was measured.

[0119] Mooney Viscosity Measurements were performed in accordance with ASTM D1646-15 and JIS K6300-1:2013 at a temperature of 100°C.

[0120] Magnesium oxide particle size The 10% particle size (cumulative 10% particle size on a volume basis), 50% particle size (cumulative 50% particle size on a volume basis), and 90% particle size (cumulative 90% particle size on a volume basis) of magnesium oxide are measured using the laser diffraction / scattering method (ultrasonication method). 70 ml of ethanol is added to 0.700 g of magnesium oxide, and ultrasonication is performed for 3 minutes to prepare a sample solution. Methanol is added to the sample supply device of the laser diffraction particle size distribution analyzer, and the methanol is circulated within the sample supply device, and the sample solution is added. Measurements are performed after 1 minute (30 seconds x 2 times), and the average value of the measurements from the two measurements is taken as the particle size.

[0121] Tensile Modulus The thermoplastic polymer compositions produced in the Examples and Comparative Examples were compression molded under conditions of 260°C and 5 MPa using a hot press machine to prepare sheet-like test pieces with a thickness of 0.5 mm, and then dumbbell-shaped test pieces with a gauge length of 3.18 mm were punched out from the sheet-like test pieces using an ASTM D638 Type V dumbbell. Using the obtained dumbbell-shaped test pieces, a tensile test was performed at 25°C and a tensile speed of 50 mm / min in accordance with ASTM D638 using an autograph (Shimadzu Corporation, AGS-J 5kN) to measure the tensile modulus of elasticity.

[0122] Tensile strength and elongation at break The thermoplastic polymer compositions produced in the Examples and Comparative Examples were compression molded under conditions of 260°C and 5 MPa using a hot press machine to prepare sheet-like test pieces with a thickness of 2 mm, from which dumbbell-shaped test pieces with a thickness of 2 mm and a width of 5 mm were punched out. Using the obtained dumbbell-shaped test pieces, a tensile test was performed under conditions of 50 mm / min using an autograph (Shimadzu Corporation, AGS-J 5kN) in accordance with JIS-K6301, and the tensile breaking strength and tensile breaking elongation at 25°C were measured.

[0123] MIT value The pellets of the thermoplastic polymer compositions produced in Examples 1-2 and Comparative Examples 1-3 were molded into extruded sheets using a kneading extrusion pelletizer (model: IMC-9413, manufactured by Imoto Machinery Co., Ltd., Φ14, L / D20) equipped with a T-die with a width of 150 mm under conditions of a die temperature of 250°C and 60 rpm. The extruded sheets were cut to produce test pieces with a width of 12.7 mm, a length of 90 mm, and a thickness of 0.5 mm. The length direction of the test pieces was perpendicular to the extrusion direction. Furthermore, the thermoplastic polymer compositions produced in Example 3 and Comparative Example 4 were compression molded under conditions of 260°C and 5 MPa using a hot press to prepare test pieces measuring 12.7 mm in width, 90 mm in length and 0.5 mm in thickness. The test piece was attached to an MIT tester (model number 12176, manufactured by Yasuda Seiki Seisakusho Co., Ltd.), and the test piece was bent under the conditions of a load of 1.5 kg, a bending angle of 135 degrees on the left and right, and a bending frequency of 175 times / min, and the number of times (MIT value) until the test piece broke was measured five times. The average value of the five measurements was taken as the MIT value.

[0124] Rate of change of pressure A breaker plate with a mesh (80 / 325 / 80) inserted therein was installed between the die and head of the extruder, and a pressure gauge was installed upstream of the head to measure the pressure of the thermoplastic polymer composition (kneaded product) in the die.

[0125] The rate of change in pressure was calculated using the following formula: Rate of change of pressure (%) = (X t -X0) / X0 X0: Pressure applied to the mixture in the die at the start of extrusion (MPa) X t : Pressure applied to the mixture in the die t minutes after the start of extrusion (MPa)

[0126] In the examples and comparative examples, the following materials were used.

[0127] Magnesium oxide (C1) "Kyowamag (registered trademark) MF-150" (manufactured by Kyowa Chemical Industry Co., Ltd.) MgO content (purity): 99.6% by mass 10% particle size: 0.35μm 50% particle size: 0.72μm 90% particle size: 1.36μm

[0128] Magnesium oxide (C2) "Kyowamag (registered trademark) 150" (manufactured by Kyowa Chemical Industry Co., Ltd.) MgO content (purity): 98.0% by mass 10% particle size: 1.99μm 50% particle size: 4.46μm 90% particle size: 11.9μm

[0129] Magnesium oxide (C3) "Magsarat (registered trademark) ST" (Kyowa Chemical Industry Co., Ltd.) MgO content (purity): 98.0% by mass 10% particle size: 2.03μm 50% particle size: 4.92μm 90% particle size: 12.2μm

[0130] Magnesium oxide (C4) "Star Mag PSF-150" (manufactured by Konoshima Chemical Co., Ltd.) MgO content (purity): 99.4% by mass 10% particle size: 0.31μm 50% particle size: 0.58μm

[0131] Example 1 100 parts by mass of VdF rubber (VdF / TFE / HFP=50 / 20 / 30 molar ratio, Mooney viscosity at 100°C 87), 0.3 parts by mass of crosslinking agent bisphenol AF (manufactured by Daikin Industries, Ltd.), 1.45 parts by mass of a solid solution of bisphenol AF and a crosslinking accelerator not containing chlorine atoms (benzyltriphenylphosphonium (BTP)) (BIS-AF-BTP 4:1 salt (bisphenol AF:BTP=4:1 (mass ratio)), manufactured by Central Glass Co., Ltd.), and 4 parts by mass of magnesium oxide (C1) were kneaded using an 8-inch open roll to obtain a full compound of VdF rubber.

[0132] 70 parts by mass of ETFE (ethylene / TFE=35 / 65 molar ratio, melting point 220°C, MFR (297°C) 15.0g / 10min) and 30 parts by mass of the full compound of the VdF rubber were fed to a twin-screw extruder (manufactured by Technobel Co., Ltd., device name: KZW15TW-60MG-NH(-700), aperture 15mm, L / D60) and melt-kneaded under conditions of a cylinder temperature of 280°C and a screw rotation speed of 400rpm to produce pellets of a thermoplastic polymer composition. Using the obtained pellets, various physical properties were measured by the above-mentioned methods. The results are shown in Table 1.

[0133] Comparative Example 1 Except for changing magnesium oxide (C1) to magnesium oxide (C2), pellets of a thermoplastic polymer composition were produced in the same manner as in Example 1. The results are shown in Table 1.

[0134] Comparative Example 2 Except for changing magnesium oxide (C1) to magnesium oxide (C3), pellets of a thermoplastic polymer composition were produced in the same manner as in Example 1. The results are shown in Table 1.

[0135] [Table 1]

[0136] The thermoplastic polymer composition of Comparative Example 1 has the same components as the thermoplastic polymer composition of Example 1, except that it contains magnesium oxide (C2) having a 10% particle size on a volume basis of 1.99 μm instead of magnesium oxide (C1). As shown in Table 1, the MIT value of the thermoplastic polymer composition of Example 1 is 1.20 times the MIT value of the thermoplastic polymer composition of Comparative Example 1, and it was found to have excellent flex resistance.

[0137] Furthermore, as shown in Table 1, in the method for producing the thermoplastic polymer composition of Example 1, the rate of change in pressure when the kneaded material was continuously extruded from the die for 60 minutes was less than 5%, indicating that the method can be produced with high productivity.

[0138] Example 2 Pellets of a thermoplastic polymer composition were produced in the same manner as in Example 1, except that 80 parts by mass of ETFE (ethylene / TFE=35 / 65 molar ratio, melting point 220°C, MFR (297°C) 28.9g / 10min) and 20 parts by mass of a full compound of VdF-based rubber were melt-kneaded at a screw rotation speed of 300 rpm. The results are shown in Table 2.

[0139] Comparative Example 3 Except for changing magnesium oxide (C1) to magnesium oxide (C2), pellets of a thermoplastic polymer composition were produced in the same manner as in Example 2. The results are shown in Table 2.

[0140] [Table 2]

[0141] Example 3 A full compound of VdF rubber was obtained in the same manner as in Example 1, except that magnesium oxide (C1) was changed to magnesium oxide (C4).

[0142] 59.9 g of ETFE (ethylene / TFE=35 / 65 molar ratio, melting point 220°C, MFR (297°C) 15.0 g / 10 min) was added to a Labo Plastomill (manufactured by Toyo Seiki Seisakusho Co., Ltd.) and after visually confirming that it was sufficiently melted, 25.7 g of the full compound of VdF rubber was added and the screw speed was increased to 100 rpm. The mixture was stirred until the torque stabilized after the dispersion and reaction had progressed sufficiently, and a thermoplastic polymer composition was produced. The results are shown in Table 3.

[0143] Comparative Example 4 A thermoplastic polymer composition was produced in the same manner as in Example 3, except that magnesium oxide (C2) was used instead of magnesium oxide (C4). The results are shown in Table 3.

[0144] [Table 3]

[0145] Experimental Example 1 A bulk thermoplastic polymer composition was produced in the same manner as in Example 3, except that magnesium oxide (C4) was changed to magnesium oxide (C1). The obtained thermoplastic polymer composition was cut with a microtome, and the cut surface was observed using a scanning electron microscope (SEM) (SU-8020 manufactured by Hitachi High-Tech Corporation, accelerating voltage 5 KV). An image of the cut surface is shown in FIG.

[0146] Experimental Example 2 The bulk thermoplastic polymer composition obtained in Comparative Example 4 was cut with a microtome, and the cut surface was observed with a scanning electron microscope (SEM). An image of the cut surface is shown in FIG.

[0147] As shown in the image of Figure 2, agglomerates are observed in the thermoplastic polymer composition (Comparative Example 4) containing magnesium oxide with a volume-based 10% particle size exceeding 1.0 μm. Furthermore, an element mapping image (not shown) of magnesium element obtained at the same time revealed that the agglomerates contained magnesium element. Therefore, it is presumed that the agglomerates were formed of magnesium oxide. On the other hand, as shown in the image of Figure 1, no agglomerates are observed in the thermoplastic polymer composition (Experimental Example 1) containing magnesium oxide with a volume-based 10% particle size of 1.0 μm or less, and it is understood that each component is sufficiently dispersed.

Claims

1. A thermoplastic polymer composition comprising a fluororesin (A), a crosslinked fluororubber (B) and magnesium oxide (C), The fluororesin (A) is a copolymer containing ethylene units and tetrafluoroethylene units, the crosslinked fluororubber (B) is obtained by dynamically crosslinking the fluororubber (b) in the presence of the fluororesin (A), magnesium oxide (C) and a crosslinking agent (D) under a melting condition of the fluororesin (A); The magnesium oxide (C) has a volume-based 10% particle size of 0.1 to 0.6 μm and a volume-based 50% particle size of 1.0 μm or less; The mass ratio ((A) / (B)) of the fluororesin (A) to the crosslinked fluororubber (B) is 50 / 50 to 95 / 5. Thermoplastic polymer composition.

2. The thermoplastic polymer composition according to claim 1, wherein the content of the magnesium oxide (C) is 0.01 to 10 parts by mass based on 100 parts by mass of the fluororubber (b).

3. 3. The thermoplastic polymer composition according to claim 1, wherein the melting point of the fluororesin (A) is 160 to 320°C.

4. 3. The thermoplastic polymer composition according to claim 1, wherein the fluororubber (b) is a partially fluorinated rubber.

5. 3. The thermoplastic polymer composition according to claim 1 or 2, wherein the fluororubber (b) is at least one selected from the group consisting of vinylidene fluoride / hexafluoropropylene-based fluororubbers, vinylidene fluoride / tetrafluoroethylene / hexafluoropropylene-based fluororubbers, and tetrafluoroethylene / propylene-based fluororubbers.

6. 3. The thermoplastic polymer composition according to claim 1, wherein the crosslinking agent (D) is at least one selected from the group consisting of polyhydroxy compounds, polyamine compounds and peroxides.

7. 3. The thermoplastic polymer composition according to claim 1 or 2, which exhibits an MIT value 1.2 times or more as compared with the MIT value of a thermoplastic polymer composition having the same components except that it contains magnesium oxide having a 10% particle size on a volume basis of 1.99 μm instead of magnesium oxide (C).

8. the fluororesin (A) is a copolymer having a molar ratio of ethylene units to tetrafluoroethylene units (ethylene units / TFE units) of 10 / 90 to 62 / 38 and a content of ethylene units and tetrafluoroethylene units of 90 to 100 mol % based on the total monomer units; the fluororubber (b) is a vinylidene fluoride / hexafluoropropylene-based rubber having a molar ratio of vinylidene fluoride / hexafluoropropylene of 45-85 / 55-15, or a vinylidene fluoride / tetrafluoroethylene / hexafluoropropylene-based fluororubber having a molar ratio of vinylidene fluoride / tetrafluoroethylene / hexafluoropropylene of 40-80 / 10-35 / 10-35, The magnesium oxide (C) has a volume-based 10% particle size of 0.1 to 0.4 μm; The crosslinking agent (D) is a polyhydroxy compound; a mass ratio ((A) / (B)) of the fluororesin (A) to the crosslinked fluororubber (B) is 60 / 40 to 85 / 15; The melt flow rate (297°C) of the thermoplastic polymer composition is 1.0 to 30 g / 10 min. The thermoplastic polymer composition according to claim 1 or 2.

9. 3. The thermoplastic polymer composition according to claim 1 or 2, in the form of pellets.

10. A molded article obtained by molding the thermoplastic polymer composition according to claim 1 or 2.

11. 11. The molded article according to claim 10, which is a tube or a hose.

12. A method for producing the thermoplastic polymer composition according to claim 1 or 2, comprising the steps of: A production method comprising the steps of: kneading a fluororubber composition containing a fluororesin (A), a fluororubber (b), magnesium oxide (C) and a crosslinking agent (D) in an extruder equipped with a cylinder and a die at a temperature equal to or higher than the melting point of the fluororesin (A); and extruding the resulting kneaded mixture through the die to obtain pellets of the thermoplastic polymer composition.

13. The method according to claim 12, wherein when the kneaded material is continuously extruded through the die for 60 minutes, a rate of change in pressure calculated by the following formula is 5% or less. Pressure change rate (%) = (X 60 -X 0 ) / X 0 X 0 : Pressure (MPa) applied to the kneaded material in the die at the start of extrusion X 60 : Pressure (MPa) applied to the kneaded material in the die 60 minutes after the start of extrusion

Citation Information

Patent Citations

  • Special magnesium oxide for fluororubber and preparation method thereof

    CN104087030A

  • Composite metal oxide, its production and its use

    JP1994157032A

  • Fixing roller

    JP1998048989A

  • Method for producing composition including fluorine resin and pulverized crosslinked fluorine rubber

    JP2013023629A

  • Magnesium oxide particle, resin composition, rubber composition and molding

    JP2016106160A